2017
DOI: 10.1016/j.neuron.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Left Habenula Mediates Light-Preference Behavior in Zebrafish via an Asymmetrical Visual Pathway

Abstract: Habenula (Hb) plays critical roles in emotion-related behaviors through integrating inputs mainly from the limbic system and basal ganglia. However, Hb also receives inputs from multiple sensory modalities. The function and underlying neural circuit of Hb sensory inputs remain unknown. Using larval zebrafish, we found that left dorsal Hb (dHb, a homolog of mammalian medial Hb) mediates light-preference behavior by receiving visual inputs from a specific subset of retinal ganglion cells (RGCs) through eminentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
139
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(153 citation statements)
references
References 67 publications
13
139
0
1
Order By: Relevance
“…Larvae were then returned to E3 medium. Survival was comparable to that of non-enucleated controls (> 95%) confirming previous reports in which development of the larva was no affected by single-eye enucleations [52, 54, 55, 56]. …”
Section: Methodssupporting
confidence: 87%
“…Larvae were then returned to E3 medium. Survival was comparable to that of non-enucleated controls (> 95%) confirming previous reports in which development of the larva was no affected by single-eye enucleations [52, 54, 55, 56]. …”
Section: Methodssupporting
confidence: 87%
“…Connectivity from this nucleus to the habenula has been shown by several groups 24, 28, 29 . The neuropil of the nucleus rostrolateralis may include the arborization field AF4 24, 30 .…”
Section: Discussionmentioning
confidence: 83%
“…This was confirmed recently by Zhang et al . 29 , who showed that retinal ganglion cells innervating AF4 expressing opn4xa .…”
Section: Discussionmentioning
confidence: 99%
“…The left dHb was recently shown to receive visual input from a specific type of retinal ganglion cell via EmT afferent connections [26]. In agreement with these differences in connectivity, the left and right dHb differentially respond to light and odor cues [2628]. Since only 20% of left dHb neurons are light-responsive [27], most likely they comprise a distinct set than those that attenuate fear.…”
Section: Discussionmentioning
confidence: 94%
“…Notably, axons from a bilaterally distributed subset of olfactory mitral cells terminate in a discrete region of only the right dHb [25]. The left dHb was recently shown to receive visual input from a specific type of retinal ganglion cell via EmT afferent connections [26]. In agreement with these differences in connectivity, the left and right dHb differentially respond to light and odor cues [2628].…”
Section: Discussionmentioning
confidence: 99%